IMPLEMENTASI STRATEGI VALUE CHAIN REENGINEERING UNTUK MEMPERKUAT RESILIENSI USAHA MIKRO PADA MICROSTOCK GOLDEN BITES - Febrianto, Gustaf Naufan; Pristiana, Ulfi; Dutahatmaja, Angga; Brahmayanti, Ida Ayu Sri; Riyadi, Slamet (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Micro-enterprises like Microstock Golden Bites face challenges in maintaining business sustainability due to low value chain efficiency. Increasing competitiveness through value chain optimization is crucial for strengthening business resilience amidst intense market competition.Objective Implementing a Value Chain Reengineering strategy to increase operational efficiency, strengthen competitiveness, and enhance the resilience of micro-enterprises through improvements to production, distribution, and marketing processes.